2019
DOI: 10.1111/add.14756
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of injection drug use among people who use drugs in Vancouver, Canada, 1996–2017: growth mixture modeling using data from prospective cohort studies

Abstract: Background and aims Injection drug use patterns are known to change over time, although such long‐term changes have not been well described. We sought to characterize longitudinal trajectories of injection drug use and identify associated factors. Design Data were derived from the Vancouver Injection Drug Users Study and AIDS Care Cohort to evaluate the Exposure to Survival Services study, two prospective cohorts involving people who inject drugs in Vancouver, Canada between 1996 and 2017. Growth mixture model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Previous studies of post‐release IDU reported no association with age [17, 18]. Studies of community‐recruited people who inject drugs have reported inconsistent findings, with findings showing both increased [27–29] and decreased [30] rates of IDU cessation among younger adults and reduced risk of IDU resumption following cessation among older people [31]. Our results of reduced odds of resumption for younger participants, but also incrementally lower odds as participants age beyond 39 years, offer insights that potentially bridge these paradoxical findings.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of post‐release IDU reported no association with age [17, 18]. Studies of community‐recruited people who inject drugs have reported inconsistent findings, with findings showing both increased [27–29] and decreased [30] rates of IDU cessation among younger adults and reduced risk of IDU resumption following cessation among older people [31]. Our results of reduced odds of resumption for younger participants, but also incrementally lower odds as participants age beyond 39 years, offer insights that potentially bridge these paradoxical findings.…”
Section: Discussionmentioning
confidence: 99%
“…Trajectories of use vary among people who use drugs, ranging from persistent use or declining use to cessation and relapse or sustained cessation. Studies of people who inject opioids, for example, have identified factors that, to some extent, are predictive of these trajectories (19). Being in a stable relationship, for instance, has been associated with early cessation (highlighting the importance of social support).…”
Section: Making Addiction Treatment More Dynamic and Personalizedmentioning
confidence: 99%
“…Currently, approximately two million Americans have an opioid use disorder (OUD; SAMHSA, 2019 ), and 46,802 died from an opioid overdose in 2018 alone, a fourfold increase from 2002 ( Hedegaard et al, 2020 ). Aside from overdose and other adverse events, OUD is a highly debilitating and chronic condition for many ( Dong et al, 2019 ; Rhee & Rosenheck, 2019 ). Medications for OUD (MOUD), primarily the opioid agonist methadone and partial agonist buprenorphine, are the gold-standard treatment for OUD and are life saving ( Connery, 2015 ).…”
mentioning
confidence: 99%